Local Action Groups and Sustainable Development Agenda: Case Study of Regional Perspectives From Czechia - Vávra, Jan; Dlouhá, Jana; Pospíšilová, Marie; Pělucha, Martin; Šindelářová, Iveta; Dvořáková Líšková, Zuzana; Hartych, Marek; Dlouhý, Jiří; Cudlínová, Eva (Frontiers in Sustainability, 2022)
The United Nation’s 2030 Agenda for Sustainable Development is generally accepted as an overarching framework to cope with various global challenges. Many of them are manifested locally and need to be solved at the regional or local level. National strategies of regional development and top-down funding are important drivers of the activities of various regional actors. However, integration of the regional development strategies and the sustainable development agenda is not straightforward and may fail to acknowledge the local context and potential for bottom-up activities. In the European Union’s (EU) context, the Local Action Groups (LAGs) are an important driving force of regional development but little is known about their perception of the sustainable development agenda. The article presents a research case study of Czech LAGs realized in 2021. LAGs were approached with questionnaires focusing on their understanding of the sustainable development agenda and their own role in the process of its implementation. In this paper we show that the LAGs’ representatives are aware of the sustainable development concept and work with relevant governmental strategies but they feel that they cannot contribute to the fulfilment of many particular Sustainable Development Goals (SDGs), especially those related to the environment. This contrasts with their reflection of the goals with an economic and social focus in which they feel relatively more empowered, especially in education. Our findings reveal that there is a high risk of mismatch between the bottom-up potential of LAGs for regional sustainable development and top-down conditions of national strategies. The results of the research contribute to the contemporary discussions about the SDGs and regional development and thus could be used by both academics and practitioners. Notably, national policymakers and regional authorities could benefit from our insights into LAGs’ perceived position with the problem of implementing SDGs the problem.